1992
DOI: 10.1093/jac/30.6.843
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of imipenem versus piperacillin plus gentamicin in the initial management of febrile neutropenic patients with haematological malignancies

Abstract: Three-hundred and twelve episodes of fever in 234 neutropenic patients with haematological malignancies were treated empirically with either imipenem or a combination of piperacillin and gentamicin. There were no significant differences in the percentages of patients responding to therapy at either 72 h (59% and 56% of assessable episodes in the imipenem and combination groups respectively) or at the end of treatment (55% and 53% of assessable episodes in the imipenem and combination groups respectively). Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 0 publications
1
14
1
1
Order By: Relevance
“…Empirical monotherapy in treating febrile neutropenic cancer patients is attractive because of its ease of handling and potentially lower toxicity, but has been controversially discussed especially because of resistance problems [25,26]. Monotherapy with imipenem, a potent beta-lactam antibiotic, or with ceftazidime, a third-generation cephalosporin, has been successfully tested in a number of trials in febrile neutropenic adults [4,6,7,20,[27][28][29][30] and pediatric cancer patients [8,31] and is also approved by the Infectious Diseases Society of America (IDSA) [32]. A retrospective analysis of several prospective open and randomized trials evaluating imipenem in neutropenic cancer patients did not show the emergence of drug resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical monotherapy in treating febrile neutropenic cancer patients is attractive because of its ease of handling and potentially lower toxicity, but has been controversially discussed especially because of resistance problems [25,26]. Monotherapy with imipenem, a potent beta-lactam antibiotic, or with ceftazidime, a third-generation cephalosporin, has been successfully tested in a number of trials in febrile neutropenic adults [4,6,7,20,[27][28][29][30] and pediatric cancer patients [8,31] and is also approved by the Infectious Diseases Society of America (IDSA) [32]. A retrospective analysis of several prospective open and randomized trials evaluating imipenem in neutropenic cancer patients did not show the emergence of drug resistance [33].…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Controlled studies have shown that no differences are demonstrable with regard to response to therapy when the results of combined antibiotic therapy are compared with those of single-agent therapy. 3,4 Ceftazidime, a third-generation cephalosporin, has been examined in a number of studies as single-agent therapy 5 and combined therapy. 6 Ceftazidime displays very good efficacy against Gramnegative bacteria including Pseudomonas aeruginosa but, like most cephalosporin antibiotics, only limited activity against Gram-positive bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports demonstrated that the efficacy of imipenem monotherapy was comparable to that of a double ␀-lactam therapy or an extended ␀-lactam combined with an aminoglycoside. 8,[11][12][13] Others showed comparable efficacy of imipenem to aztreonam and cefoperazone sulbactam in the presence of vancomycin (Bodey et al, unpublished data, and published studies [3][4][5]14 ). The optimum dose of imipenem has also been evaluated in the setting of febrile neutropenia.…”
Section: Discussionmentioning
confidence: 99%